2009
DOI: 10.2152/jmi.56.26
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols prevent clinorotation-induced expression of atrogenes in mouse C2C12 skeletal myotubes

Abstract: Unloading, as occurs in long-term bed rest, immobilization, and weightlessness, causes rapid and marked muscle atrophy (1, 2). We previously reported that unloading, including spaceflight as well as tail-suspension, stimulated ubiquitination of various proteins, including myosin heavy chain (MHC), and accumulation of MHC degradation fragments in atrophied rat gastrocnemius muscle (3). Recent studies demonstrated that two ubiquitin-protein ligases (E3s), atrogin-1/MAFbx and MuRF1, are critical in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…In C2C12 myotubes ERK activation resulted in reduced myotube size [16], while ERK inhibition induced a hypertrophic phenotype similar to that elicited by IGF-1 [16]. Similarly, C2C12 myotube cultures subjected to 3D-clinorotation showed an overexpression of both atrogin-1 and MuRF1 ubiquitin ligases, associated with increased levels of phosphorylated ERK [26].…”
Section: Discussionmentioning
confidence: 85%
“…In C2C12 myotubes ERK activation resulted in reduced myotube size [16], while ERK inhibition induced a hypertrophic phenotype similar to that elicited by IGF-1 [16]. Similarly, C2C12 myotube cultures subjected to 3D-clinorotation showed an overexpression of both atrogin-1 and MuRF1 ubiquitin ligases, associated with increased levels of phosphorylated ERK [26].…”
Section: Discussionmentioning
confidence: 85%
“…EC is found in cacao beans and has the highest content of catechins among foods [7] and is made up circa 2–5% of total dry weight of green tea [8]. Anti-oxidative nutrients including EC and catechin, suppress atrogene expression in skeletal muscle cells, possibly through the inhibition of ERK signaling, resulting in prevention of unloading-mediated muscle atrophy [9]. It has been reported that EC, the main component present in dark chocolate, reduces the risk to develop cardiovascular diseases and myocardial injury [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro assays, resveratrol reduced skeletal muscle atrophy, enhanced glucose uptake, inhibited NFkB-mediated protein degradation, and improved muscle function [53], [54], [55]. EGCG reduced oxidative stress in C2C12 cells, thereby attenuating the expression of atrogin-1 and MuRF-1, two muscle atrophy-related ubiquitin ligases [52]. EGCG also abrogated the expression of lipofuscin, a marker of oxidative stress, when subcutaneously injected into mdx mice from birth, resulting in improved muscle function, force, and physiology [56].…”
Section: Resultsmentioning
confidence: 98%
“…Two natural products that reduce oxidative stress are resveratrol, present in red wine and peanuts [51] and epigallocatechin-3-gallate (EGCG), the primary polyphenol in green tea [52]. In in vitro assays, resveratrol reduced skeletal muscle atrophy, enhanced glucose uptake, inhibited NFkB-mediated protein degradation, and improved muscle function [53], [54], [55].…”
Section: Resultsmentioning
confidence: 99%